ANALISIS PENGARUH WORD OF MOUTH, DISKON DAN MOTIVASI HEDONIS TERHADAP PEMBELIAN IMPULSIF PRODUK FASHION PADA KONSUMEN WANITA - Erdiana, Atty; Lestari, Lestari - (Surakarta Management Journal, 2023)
Companies can survive and achieve high profitability if they are able to identify and satisfy the needs and desires of their consumers, so companies must always observe the behavior of these consumers. One of the consumer needs that must be met is clothing, bags or shoes, where these products are called fashion products which change very quickly. To buy this product, the role of female consumers is usually greater than that of male consumers, female consumers tend to be more detailed and more emotional in making decisions to buy it. Purchases of these fashion products sometimes appear suddenly or without being planned in advance (impulse purchases). Consumers usually follow existing trends, therefore there are several factors that are expected to influence them, including: word of mouth, discounts and hedonic motivation. The population of this study is all consumers of fashion products in Malang, with sample criteria: women, at least 17 years old and have a role as decision makers in buying fashion products.            To determine the effect of the independent variable on the dependent and the effect of each variable, multiple linear regression techniques and the t test were used. The results showed that word of mouth had a significant effect on impulsive purchases, discounts had a significant effect on impulsive purchases, hedonic motivation had no significant effect on impulsive purchases, and discounts were the dominant variable on impulsive purchases